Aplikasi Tandon-Filter untuk meningkatkan Kualitas dan Kuantitas Garam dalam Teknologi Greenhouse Salt Tunnel di Pantai Selatan dan Utara Jawa Timur - Amin, Abd. Aziz; Salamah, Lutfi Nimatus; Zamzami, Ilham Misbakudin Al; Susanti, Yogita Ayu Dwi; Yanuar, Adi Tiya; Kurniawan, Andi (Universitas Trunojoyo Madura, 2024)
Salt is an essential commodity that concerns the livelihood of society and cannot be substituted by other commodities. East Java is the largest salt-producing center in Indonesia. The results of community salt production often still have NaCl content 95%. To achieve salt production results with NaCl quality 96%, research, and technology development are needed to eliminate impurities and improve the quality of the salt produced. One of the technologies being developed is the utilization of reservoirs and raw water filters. This research aims to analyze the application of reservoir and filter technology in improving the quality and quantity of salt production on the South and North Coasts of East Java using greenhouse salt tunnels. The results of this study indicate that the dynamics of environmental parameters and the quality of raw water on the South and North Coasts of East Java affect the results of the salt production process. The quality and quantity tests of salt with reservoir and filter application on the South Coast of East Java show NaCl quality of 98.13%, water content of 5.44%, and whiteness presentation value of salt 80.5% with production quantity of 7 kg/m². In trials on the North Coast of East Java, the salt quality was 98.25%, water content was 5.37%, and the whiteness percentage value of salt was 79%, with a salt production quantity of 7.8%. This research indicates that reservoir and filter technology can improve the quality and quantity of salt according to the characteristics of the South Coast and North Coast of East Java.